ANALISIS NILAI OVERALL EQUIPMENT EFECTIVENESS (OEE) SEBAGAI LANGKAH PENINGKATAN EFEKTIFITAS MESIN PELLET MILL DI PT. NI CIBITUNG - Purnama, Billy Zaelany (Operations Excellence: Journal of Applied Industrial Engineering, 2016)
Abstract Demands for wood pellets as an alternative energy source of the country of Taiwan, Japan and Korea became one of the main factors for the PT. NI to increase productivity by utilizing production equipment as effectively as possible. Implementation of preventive maintenance is still not optimal because Pelletiser still often damaged. Pelletiser damage caused downtime large enough and also will reduce production capacity, which in turn led to delays in meeting the needs of consumers.The purpose of this study was to measure the value of OEE, determine the magnitude of each factor Six big losses that affect the value of OEE, and analyzes the factors that cause the main as a basis for improvement. Based on data processing, value of OEE is still below the targets to be achieved by the company amounted to 76.95%. From the calculation of the Six Big Losses, factors that provide the most significant influence on the effectiveness of the machine is Equipment Failure . OEE values and Losess Big Six factors are the basis of the proposed improvements is given to PT.NI. Keyword: Downtime, Equipment Failures Losses, Overall Equipment Effectiveness, Performance